Numerical simulation on geosystem Thermal-Hydro-Mechanical-Chemical coupling: A review - Cheng Hsin Liu (21797546) (2025)
With the increasing demand for efficient and safe underground storage of CO2 and hydrogen, understanding the complex interactions in geological systems has become a key research focus. This review paper provides a systematic overview of numerical simulation techniques used to model multi-field coupling in geosystems, particularly Thermal-Hydro-Mechanical-Chemical (THMC) interactions relevant to Carbon Capture, Utilization, and Storage (CCUS), and Underground Hydrogen Storage (UHS). The review summarizes the governing equations of THMC processes, including stress balance, mass conservation, energy transfer, and chemical reactions, while discussing various coupling schemes such as fully coupled, iterative, and loose approaches for their applicability and computational efficiency. Furthermore, different numerical methods, including continuum media and discontinuum media methods, are evaluated based on their strengths and limitations in multi-field coupling simulations. Challenges such as high computational costs, effective mesh strategies, handling non-linearities, and the integration of advanced technologies like machine learning are highlighted. The paper concludes by identifying key research gaps and suggesting future directions to enhance the accuracy and efficiency of THMC modeling in geological storage systems. Other Information Published in: Geoenergy Science and Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.geoen.2025.214059